Georeferencing of adolescents with malocclusion in a capital of Southern Brazil (Research, Society and Development, 2021)
The aim of this study was to analyze the prevalence and to georeference the malocclusion traits in adolescents in the city of Curitiba, Paraná, Brazil. Data from a previous cross-sectional study with 538 adolescents aged 10 to 14 years were used. In addition, the following variables were used: gender, Health District (HD) of residence, and presence and malocclusion traits. Fisher’s Exact Test, georeferencing, and kernel mapping were used for data evaluation. Malocclusion was observed in 52.4% of individuals, and the most prevalent occlusal trait was deep bite (22.7%), followed by excessive overjet (19.9%), anterior crowding (8.0%), posterior crossbite (6.5%), anterior open bite (4.8%), and anterior crossbite (1.7%). Malocclusion was not associated with gender (p = 0.389) or HD (p = 0.079). However, when stratified by gender, the deep bite prevailed among male. The highest malocclusion trait’s prevalence was observed in the HDs of Cajuru, Pinheirinho, Boa Vista, and Cidade Industrial de Curitiba. Despite the absence of significant differences in relation to gender and HD, the prevalence of malocclusion traits in the sample studied was high, especially for deep bite. Additionally, georeferencing proved to be useful for identifying the distribution of malocclusion in Curitiba.